Synthesis of 5-Halo-4H-1,3-oxazine-6-amines by a copper-mediated domino reaction - Hashmi, A. Stephen K.; Schuster, Andreas M.; Zimmer, Marc; Rominger, Frank (Chemistry - a European journal, 2011)
Three become one! In one copper-mediated step, three simple components, including a propargylcarboxamide, a protected amine, and a source of chloride, assemble to give highly functionalized oxazines, which are interesting building blocks for the synthesis of other aminooxazine derivatives (see scheme; R1=range of aryl or alkyl groups, R2=alkyl, EWG=electron-withdrawing group).
Gesehen am 07.09.2022